LncRNA MALAT1/miR-181a-5p affects the proliferation and adhesion of myeloma cells via regulation of Hippo-YAP signaling pathway. Issue 19 (2nd October 2019) - Sun, Yanbei; Jiang, Tingxiu; Jia, Yongqing; Zou, Jingyun; Wang, Xiaoxiao; Gu, Weiying
ABSTRACT: Multiple myeloma (MM) is a plasma cells malignant proliferative disease, especially in aged people. LncRNAs have been considered as important regulators in MM. This research was to study the effect of LncRNA MALAT1 on the proliferation and adhesion of myeloma cells and whether Long non-coding RNAs MALAT1(LncRNA MALAT1) plays its regulative role through Hippo-YAP signaling pathway by targeting miR-181a-5p. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) analysis was used to detect the LncRNA MALAT1/miR-181a-5p expression and improve the transfection efficiency. Western blot analysis was used to analyze the expression of proliferation and apoptosis related proteins and Hippo-Yes-associated protein (YAP) signaling pathway related proteins. Cell proliferative ability and cell apoptosis were respectively determined by Cell Counting Kit-8 (CCK-8) assay and flow cytometry analysis. ELISA assay was for the determination of adherence factors. Immunohistochemistry was to detect the expression of proliferation and adhesion related proteins. LncRNA MALAT1 targeting gene was determined by Dual-luciferase reporter assay. LncRNA MALAT1 was increased in MM cells and LncRNA MALAT1 interference could inhibit cell proliferation and promote cell apoptosis with the changes in the related proteins. Also, LncRNA MALAT1 interference could inhibit cell adhesion through Hippo-YAP signaling pathway. MiR-181a-5p was demonstrated to be a target of LncRNA MALAT1 and miR-181a-5p overexpression could also regulate the changes in cellular behavior in accordance with the LncRNA MALAT1 interference. In addition, LncRNA MALAT1 interference could decrease the expression of miR-181a-5p and inhibit the growth of tumor. In conclusion, this study showed that LncRNA MALAT1 interference inhibited the proliferation and adhesion of myeloma cells by the up-regulation of miR-181a-5p through activating the Hippo-YAP signaling pathway.